2006
DOI: 10.2193/0022-541x(2006)70[255:eaaihe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Animal Abundance in Heterogeneous Environments: An Application to Aerial Surveys for Dugongs

Abstract: The probability of detecting an animal in a sampled area during a survey consists of 2 components: 1) the probability of an animal being available for detection (availability), which can be highly variable in heterogeneous environments; and 2) the probability of an animal being detected, conditional on its being available for detection (perception). Many surveys only estimate the latter probability because modeling the availability process requires information collected external to the survey. We illustrate es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
255
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(258 citation statements)
references
References 33 publications
2
255
1
Order By: Relevance
“…Our data also highlight the need to understand perception and availability bias when using observation based monitoring and citizen science for sea turtle monitoring (Pollock et al, 2006). In particular, we found that photo quality varied across species and was also likely to be influenced by depth (of the diver and turtle) and water visibility.…”
Section: Perception and Availability Biasmentioning
confidence: 60%
“…Our data also highlight the need to understand perception and availability bias when using observation based monitoring and citizen science for sea turtle monitoring (Pollock et al, 2006). In particular, we found that photo quality varied across species and was also likely to be influenced by depth (of the diver and turtle) and water visibility.…”
Section: Perception and Availability Biasmentioning
confidence: 60%
“…Cliff 2007) or occur in shallow areas and, providing water clarity is good enough, can be recorded while they are underwater (e.g. Pollock et al 2006). However, most marine species spend a considerable amount of time deeper in the water column and are thus not visible to an observer (not 'available').…”
Section: Distance Samplingmentioning
confidence: 99%
“…A general conceptual model (Marsh and Sinclair 1989;Pollock et al 2004Pollock et al , 2006) for auditory count-based abundance estimates can be represented as:…”
Section: Introductionmentioning
confidence: 99%